A Bibliometric-Based Architectural Framework for Quantum-Safe Low Earth Orbit Satellite Systems - Muhammad Thafshir Triansha; Asep Adang Supriyadi; Syachrul Arief; Muslimin (International journal of technology and education research, 2026)
The arrival of practical quantum computing threatens the classical public-key cryptography satellite communication relies on, a threat most acute for Low Earth Orbit (LEO) satellites whose missions span many years. While post-quantum cryptography (PQC) has been studied extensively for terrestrial networks, work bringing it into LEO systems has stayed close to the algorithms and rarely connected to the system-level architecture that must run them under tight resource limits. This study addresses that gap through a bibliometric analysis of 56 Scopus-indexed publications from 2020 to 2026, using keyword co-occurrence and clustering to describe how quantum-secure satellite communication is organized. The analysis identifies four dominant thematic clusters and exposes a structural separation between PQC research and satellite architecture research, sharpest under the constrained conditions of LEO. The study proposes a Resource-Security Co-Design framework uniting lightweight cryptographic control, adaptive authentication, physical-layer entropy reinforcement, and resource-aware orchestration within one architecture, coordinating security and resource management as a single design rather than swapping PQC in as a component. An accompanying feasibility model relates computational complexity, transmission overhead, and onboard resources, setting operational boundaries within which a LEO-class satellite can sustain quantum-safe security. The central contribution is the traceable link between identified gaps and synthesized architecture.